Accuracy of Colon Capsule Endoscopy for Colorectal Neoplasia Detection in Individuals Referred for a Screening Colonoscopy. (3rd September 2019) - Voska, Michal; Zavoral, Miroslav; Grega, Tomas; Majek, Ondrej; Martinek, Jan; Tacheci, Ilja; Benes, Marek; Vojtechova, Gabriela; Drastich, Pavel; Bures, Jan; Spicak, Julius; Buckova, Barbora; et al.
Abstract : Backround . Capsule colonoscopy might present an alternative to colonoscopy for colorectal neoplasia screening. Aim . To assess the accuracy of second-generation capsule colonoscopy (CCE2) for colorectal neoplasia detection compared with conventional colonoscopy (CC). Methods . From 2011–2015, we performed a multicenter, prospective, cross-over study evaluating the use of CCE2 as a possible colorectal cancer (CRC) screening test based on the assessment of the method's characteristics (accuracy) and safety and patient acceptance of the routine. Enrolled participants fulfilled the CRC screening population criteria if they were asymptomatic, were older than 50, and had no personal or familial history of colorectal neoplasia. The primary outcome was accuracy for the detection ofpolyps ≥ 6   mm . Secondary outcomes were accuracy for all polyps, polyps ≥ 10   mm, adenomas ≥ 10   mm, and cancers, the quality of bowel cleansing, safety, and CCE2 acceptability by the screening population. Results . A total of 236 individuals were examined; 11 patients (5%) were excluded. Therefore, 225 subjects (95%) were considered in the intention-to-screen (ITS) group. A total of 201 patients (89%) completed both examinations successfully (per protocol group). In the ITS group, polyps were diagnosed during CC in 114 subjects (51%);polyps ≥ 6   mm, polyps ≥ 10   mm, andadenomas ≥ 10   mm were diagnosed in 34 (15%), 16 (7%), and 11 (5%) patients, respectively. The sensitivity of CCE2 forpolyps ≥ 6   mm, polyps ≥ 10   mm, andadenomas ≥ 10   mm was 79% (95% confidence interval (CI): 62–91%), 88% (95% CI: 62–98%), and 100% (95% CI: 72–100%), respectively. Conclusion . Second-generation capsule colonoscopy is a safe, noninvasive, and sensitive method for colorectal neoplasia detection although CC remains the preferred method for considerable proportion of subjects. CCE2 may therefore be accepted as the primary screening test for colorectal cancer screening.